Prevalence and Determinants of Pre-Hypertension among Undergraduate Preclinical Medical Students in Central Malaysia - MF, Mohd Fauzi; NA, Mat Saruan; H, Mohd Yusoff; A, Mohd Tamil (IIUM Medical Journal Malaysia, 2019)
Introduction: Pre-hypertension, a classification of blood pressure ranging from 120–139 mm Hg systolic and/ or 80–89 mm Hg diastolic, has been introduced to identify those high-risk group of developing hypertension to implement early intervention to halt disease progression. This study determines the prevalence of pre-hypertension and its determinants among undergraduate preclinical medical students in Malaysia. Materials & Methods: This was a cross-sectional study conducted among 158 registered second year medical students at one research university in central Malaysia from January to April 2018. Results: The prevalence of pre-hypertension was 20.6% among undergraduate preclinical medical students. The most respondent was female (69.9%), Malay ethnic (50.6%) who had normal body mass index (67.3%), no depression (79.5%), no anxiety (60.3%), no stress (68.6%), low physical activity level (44.9%), never smoked (95.5%), and never consumed alcohol (87.8%). Some respondents had positive family history of hypertension (43.6%) and diabetis mellitus (31.4%). After adjusted for all variables, gender (AOR=14.45, 95% CI 5.58-37.43) and depression status (AOR=6.37, 95% CI 1.29-31.49) were significantly associated with pre-hypertension. Conclusion: The prevalence of pre-hypertension among preclinical medical students was lower compared to other country, predicted by gender and depression status. However, further comprehensive multicentered studies in Malaysia with larger sample size is recommended to get more precise results in identifying determinants for pre-hypertension so that early intervention could be implemented nationwide.